Determinant of Economics Factors on The Level of Production Of Corn Farmers - Apiaty Kamaluddin; St. Hatidja; Lina Mariana (International Journal of Artificial Intelligence Research, 2022)
The research aimed to: analyze the factors affecting the production of corn farmers in Sendana District, Majene Regency. Data used were primary data and secondary data. The research population was all corn farmers in Sendana District, Majene Regency. The samples taken were 20 corn farmers in Sendana District, Majene Regency in 2021. Data collection technique used in this study employed primary data. Data collection was carried out using a questionnaire. Questionnaires distributed directly to corn farmers in Sendana District, Majene Regency. Data analysis method used descriptive statistical analysis and multiple linear regression using SPSS version 20.00. The results of the study revealed that the factors of land area, number of seeds, amount of fertilizer use and number of workers proved to have a positive effect on corn production in Sendana District, Majene Regency.